On the fishery and biology of Priacanthus hamrur Forsskal along the southwest coast of India - Premalatha, P (Indian Journal of Fisheries, 2011)
Among the unconventional finfish resources of the deep sea, priacanthids have attained greater importance along the coasts of India as an abundant group. The fishery exists almost throughout the year, but their availability in the inshore area was more during April, August and November . There was a steady increase in landings every year and they formed about 12 % of the total catch. Very little is known about their biology. A study was conducted on the availability and biological characteristics of Priacanthus hamur for a period of two years (1994-’96) based on trawling operations of F.V. Samudrika and F.V. Sagarika of the Integrated Fisheries Project, Govt, of India.The size ranged from 120-450 mm and the females were larger than males. March- April is the breeding season and the size at maturity is 175 mm for males and 190 mm for females. Gut contents indicated highly carnivorous nature.